"First report of 'Candidatus Phytoplasma pyri'-related strain causing pear decline in Argentina". (July 2019) - Fernández, Franco Daniel; Conci, Luis Rogelio
Abstract: Pear decline (PD) is an important disease affecting pear production worldwide and " Candidatus Phytoplasma pyri" (subgroup 16SrX-C) is the etiological agent of this disease. In Argentina, typical symptomatology of PD was described in pear trees located in Río Negro province. Infected trees showed leaf redness and loss of vigor. Nested PCR assays targeting the 16S rRNA gene (R16F2n/R16R2) were performed to detect the presence of phytoplasmas in ∼69% of total symptomatic samples. Virtual and actual RFLP patterns of PD Argentinean isolates shared 100% of coincidence with RFLP profile of the subgroup 16SrX-C. Moreover, identity similarity and phylogenetic analyses of partial 16S rRNA sequence showed that PD phytoplasma described in this paper is a " Ca . P. pyri"- related strain. To the best of our knowledge, this is the first report on " Ca. P. pyri" affecting pears in Argentina. Highlights: Phytoplasmas causing pear decline were detected for the first time in Argentina. Molecular identification of " Ca. Phytoplasma pyri" based on 16Sr RNA gene analysis. First evidence of " Ca. P. pyri" affecting pears in Argentina.